Clinical Education Stressors in Operating Room Students: A Qualitative Study - Norouzi, Nahid; Imani, Behzad (Investigación y Educación en Enfermería, 2021)
Objective. The aim of this study is to explain the stressors of the clinical environment from the perspective of operating room undergraduate students. Methods. The present study is a qualitative study of contractual content analysis type that was conducted in 2019 at Hamadan University of Medical Sciences. In this study, 10 undergraduate operating room students were selected by purposive sampling. Semi-structured interviews were used to collect data. Results. From the analysis of interviews, 4 main categories were extracted as the stressors of operating room students of Hamadan Paramedical School in clinical learning environment: the need to receive support from the clinical environment (Insufficient students’ skills in communicating with staff, Discrimination between paramedical students and residents, and Facilities available for training), lack of practical prerequisite skills (Contradiction between training and performance, and Lack of prerequisite knowledge for clinical practice), poor supportive and communication performance related to the instructor (Insufficient support of the instructor to the students against the medical staff, Evaluation criteria for instructors, and Treatment of instructor with students in presence of others), and psychological needs (Concerns about career prospects, Lack of motivational factors, and Lack of supportive counseling). Conclusion. The results of this study showed that Operating room students are faced with many stressors in the clinical learning environment. All stressors identified in this study affected the students’ learning in the clinical setting. Lack of support for students in the clinical environment, poor practical skills training, poor support and communication performance related to the instructor, and poor psychological support of students are the factors that cause operating room student stress in the clinical environment.